PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SQUARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII4 SMP NEGERI 25 PEKANBARU - Rio Kurniawan; Yenita Roza; Nahor Murani Hutapea (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is classroom action research that aims to improve of learning process and to improve mathematics achievement with applied the learning cooperative model Think Pair Square (TPS). The research consist of two cycles, each cycle has four stages, which are planning, implementation, observation, and reflection.The subject of this research is student of class VII4 SMP Negeri 25 Pekanbaru in academic years 2018/2019, which total of 42 students, 18 boys and 24 girls. The instruments of data collection were observation sheets and students Mathematic tests. The observation sheets were analyzed in qualitatively, while the students’ Mathematic tests were analyzed in quantitatively. The qualitative descriptive showed an improvement of learning process after to the action on the first and second cycle. Most of students were very confidenced and active in learning process, they were finished mathemathic’s problems that given, presenting the result of problems and giving the conclusion of learning. Number of students that reach Minimum Mastery Criteria increase from basic score to first test I and II. The results of this research showed an increasing of students achievement where the basic score (33,33 %) to the first test (42,85 %), the second test II (59,25 %). For the achievement of score the first test (50 %), the second test (61,90 %). Results of this research indicates that appication of the learning cooperative model Think Pair Square (TPS) can improve learning process and increase mathematics achievement of the students at class VII4 SMPN 25 Pekanbaru in academic years 2018/2019 for the subject matter algebraic form.Key Words: Mathematics Achievement, Learning Cooprative Model Think Pair Square (TPS)